2018
DOI: 10.17306/j.afs.0549
|View full text |Cite
|
Sign up to set email alerts
|

The effect of selected components of milk and ripening time on the development of the hardness and melting properties of cheese

Abstract: The recorded range of changes do not affect the nutritional values of cheese, as free fatty acid content increased only slightly with ripening time. The observed tendencies towards slower proteolysis and lipolysis reactions can be partly explained by the increasing content of dry matter (lower water availability). It was shown that the proportion of fat in milk and cheese and its protein content significantly affected the hardness and melting properties of cheese. Importantly, the proportion of casein in milk … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…It was reported that meltability and fat leakage of cheese were closely related to its content of fat that acted as a lubricant promoting heat-induced cheese melting process, but higher fat content facilitated formation of larger anisotropic fat particles that further contributed to the melting and fat leakage of cheese 28 , 29 . The higher meltability and free fat content of PC1 of this study could be mainly due to its higher fat content (27.1%, w/w) than those of PC2 (23.8, w/w) and PC3 (25.4%, w/w) (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that meltability and fat leakage of cheese were closely related to its content of fat that acted as a lubricant promoting heat-induced cheese melting process, but higher fat content facilitated formation of larger anisotropic fat particles that further contributed to the melting and fat leakage of cheese 28 , 29 . The higher meltability and free fat content of PC1 of this study could be mainly due to its higher fat content (27.1%, w/w) than those of PC2 (23.8, w/w) and PC3 (25.4%, w/w) (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the polymorphism may affect the expression of the protein, resulting in changes in milk protein content and other components of dairy goats' milk. The increase in the milk protein improves the nutritional value of milk and is also beneficial in the cheese-making process [44,45]. However, this may also have some negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…One of the simplest and most traditional methods for preserving food to increase its shelf life is the direct addition of additives which may be chemical or naturally derived preservatives. These ingredients are added to cheese in order to prevent spoilage and pathogenic microbial growth, increase shelf life, enhance organoleptic and sensory characteristics, and maintain nutritional value [91,92].…”
Section: Ripened Cheese Additivesmentioning
confidence: 99%